A polyurethane composite material containing recycled filler and preparation method thereof

By inert modification of the recycled filler and introducing composite anti-aging agents, the problem of impurities in the recycled filler causing aging of polyurethane composite materials is solved, and the product's high mechanical properties and environmental stability are achieved.

CN118667323BActive Publication Date: 2025-03-25GUANGDONG TUEN NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410856263.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-03-25
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

When polyurethane composites use recycling fillers, the impurities in the recycling fillers are highly active, which may accelerate the structural aging of the polyurethane molecular chain, leading to a decline in the mechanical properties of the product, and even problems such as appearance cracks, yellowing, and powdering.

Method used

Prepare into filler particle powder by inert modification of the recovered filler and introduce specific composite anti-aging agents, including antioxidants and ultraviolet absorbers, to the polyurethane matrix, to improve the light, moisture and heat aging performance of the product.

Benefits of technology

The mechanical properties of polyurethane composites have been significantly improved, making their mechanical properties higher than that of existing recycled polyurethane composites, and are comparable to the newly made polyurethane composites containing fillers, and have excellent environmental stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004918156740000081
    Figure BDA0004918156740000081
  • Figure BDA0004918156740000091
    Figure BDA0004918156740000091
  • Figure BDA0004918156740000092
    Figure BDA0004918156740000092
Patent Text Reader

Abstract

The invention discloses a polyurethane composite material containing recycled fillers and a preparation method thereof, belonging to the technical field of polymer materials. When preparing the polyurethane composite material of the invention, the recycled filler is firstly inertly modified to prepare filler particle powder and introduced into a polyurethane matrix, and then a specific composite anti-aging agent is introduced into the polyurethane matrix. The obtained product not only has good light, humidity and heat aging resistance, but also has excellent basic mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a polyurethane composite material containing recycled fillers and a preparation method thereof. Background Art

[0002] Rigid materials (including organic rigid materials and inorganic rigid materials) are often used as fillers to prepare polyurethane composite materials. The polyurethane composite materials containing fillers have higher mechanical indicators such as tensile strength or flexural modulus, and their wear resistance is also improved.

[0003] Rigid materials that can be used as fillers are widely available. In addition to new materials, in the recycling industry, the recycling steps of fillers are simple and the recovery rate is high. If these recycled fillers are reused in polyurethane composites, the production cost of the products will be significantly reduced (generally speaking, the mass content of fillers in polyurethane composites ranges from 5 to 25wt%). For example, the article "The Effect of Different Fillers on the Performance of Polyurethane and Its Composites"-2015 pointed out that the use of waste fiberglass as fillers to prepare polyurethane composites has better rigidity index improvement effect than some traditional rigid materials.

[0004] However, the ester bonds and urea bonds in the polyurethane chain are easily affected by external factors and then hydrolyzed or oxidatively decomposed. After the recycled filler is prepared into a polyurethane composite material, some of the impurities that originally remained are highly active and may act as photo / thermal degradation catalysts, further accelerating the structural aging of the polyurethane molecular chain, ultimately leading to a decrease in the mechanical properties of the product, and even the appearance of cracks, yellowing, powdering, etc. Summary of the invention

[0005] Based on the defects of the prior art, the purpose of the present invention is to provide a polyurethane composite material containing recycled fillers. First, the recycled filler is inertly modified to prepare a filler particle powder and introduced into a polyurethane matrix. Subsequently, a specific composite anti-aging agent is introduced into the polyurethane matrix. The resulting product not only has good resistance to light, humidity and heat aging, but also has a higher degree of mechanical property improvement than the existing recycled polyurethane composite materials, which is equivalent to that of newly prepared filler-containing polyurethane composite products.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A polyurethane composite material comprises the following components in parts by weight:

[0008] 80-90 parts of polyurethane, 10-20 parts of filler particle powder, 1-2 parts of composite anti-aging agent;

[0009] The filler particle powder is a recycled filler wrapped with modified resin;

[0010] The modified resin includes ultra-high molecular weight polyethylene and hyperbranched polyester;

[0011] The composite anti-aging agent includes an antioxidant and an ultraviolet absorber;

[0012] The antioxidant is a compound of a semi-hindered phenol antioxidant, a phosphite antioxidant and a sulfur antioxidant.

[0013] Preferably, the recycled filler includes at least one of recycled inorganic filler and recycled organic composite filler.

[0014] In the prior art, there are generally two types of recycled fillers. One is inorganic fillers recovered and separated from plastics or other industrial parts, such as recycled talcum powder, quartz powder, etc. These fillers have better theoretical reinforcement performance, but these inorganic materials have poor compatibility and processability, and are prone to local agglomeration and poor dispersion when preparing polyurethane composite materials; the other is inorganic reinforced organic composite materials such as fiberglass powder (also known as fiber reinforced plastic, generally referring to glass fiber reinforced unsaturated polyester, epoxy resin, etc.) and special high melting point plastics. Such materials generally do not require separation of the resin matrix, and only need to be simply cleaned and removed and then ground into a suitable size to complete recycling and application. However, the biggest feature of such materials is that they contain a certain amount of catalytically active impurities, especially components such as halogen flame retardants that are extremely easy to degrade. When used in the preparation of polyurethane composite materials, these components will greatly reduce the light, moisture and heat stability of the product, resulting in the product having high mechanical strength in the initial stage, but extremely poor environmental stability and limited scope of use.

[0015] To this end, in the technical solution of the present invention, the inventor firstly encapsulates these recycled fillers with a modified resin containing ultra-high molecular weight polyethylene and hyperbranched polyester to prepare filler particle powder, wherein ultra-high molecular weight polyethylene is an excellent degradation-resistant material, which will not undergo obvious degradation behavior at 315°C, so the use of this material for encapsulation can effectively avoid the impurities in the recycled filler accelerating the light and heat aging reaction of the polyurethane product; at the same time, the material has a much higher rigidity and toughness enhancement than the traditional toughening agent due to its ultra-high molecular weight, which also makes the filler particle powder prepared after the recycled filler is encapsulated have a better mechanical enhancement effect on the polyurethane composite material. On the other hand, ultra-high molecular weight polyethylene can reduce the friction between the recycled filler particles and between the recycled filler and the polyurethane matrix, so after encapsulation, the filler particle powder has good processing performance and integrity in the polyurethane composite material, and will not show obvious cracking phenomenon, and has strong stability.

[0016] However, the compatibility of ultra-high molecular weight polyethylene with polyurethane and recycled fillers is not actually high, and physical isolation alone cannot prevent some organic components in the recycled fillers from being degraded or affected by the outside world. Therefore, the inventors introduced hyperbranched polyester into the encapsulated modified resin. This new material can not only improve the compatibility of the modified resin and the recycled filler in the filler particle powder and prevent the recycled filler from leaking out, but also have a certain antioxidant protection effect. Even the compounding of hyperbranched polyester can improve the basic mechanical properties of the overall product. In addition, in the polyurethane matrix resin, the inventors also introduced three types of antioxidants, namely, specific semi-hindered phenol antioxidants, phosphite antioxidants and sulfur antioxidants. After experimental comparison, it was found that the composite of these three antioxidants has the best compatibility with ultra-high molecular weight polyethylene and hyperbranched polyester modified recycled fillers, and can significantly inhibit the catalytic effect of impurities in the recycled fillers and the degradation and oxidation effect of external environmental factors (especially water and oxygen) on the polyurethane matrix, so that the product has excellent environmental stability.

[0017] Preferably, the recycled inorganic filler is recycled titanium dioxide, and the average particle size of the recycled titanium dioxide is ≤20 μm.

[0018] More preferably, the mass content of rutile titanium dioxide in the recovered titanium dioxide is ≥50wt%.

[0019] Preferably, the recycled organic composite filler includes but is not limited to at least one of glass fiber reinforced polypropylene, glass fiber reinforced polyethylene, and glass fiber reinforced polyester.

[0020] Glass fiber reinforced plastic is a common fiberglass material and a type of reinforced rigid material that is relatively easy to recycle. This material generally has high mechanical strength and wear resistance. When 10% by mass is introduced, the mechanical properties of the polyurethane material can be improved by about 10%. On the other hand, when smaller-sized titanium dioxide contains a certain amount of rutile crystal, it will have the ability to absorb ultraviolet rays in light within a specific wavelength, thereby increasing the interface diffuse reflection of the product and further improving the stability of the product under light.

[0021] Preferably, the filler particle powder comprises the following components in parts by weight:

[0022] 80-90 parts of recycled filler and 10-20 parts of modified resin;

[0023] The modified resin is a composite of ultra-high molecular weight polyethylene and hyperbranched polyester, and the mass ratio of the two is (7:3) to (5:5).

[0024] By optimally matching the two modified resins, the prepared filler particle powder can have high uniformity and high dispersibility, which can improve the mechanical enhancement and environmental stability of the product.

[0025] Preferably, the filler particle powder has a particle size of 50 to 100 μm.

[0026] Unlike filler masterbatches, the filler particle powder of the present invention needs to maintain the size level of the recycled filler as much as possible, so it cannot be produced using the conventional formula ratio of the masterbatch. In order to make the recycled filler as dispersed as possible but evenly wrapped by the modified resin, the above formula is used to compound and prepare filler particle powder with a core-shell structure.

[0027] More preferably, the ultra-high molecular weight polyethylene is ultra-high molecular weight polyethylene GUR4056-3 produced by Celanese.

[0028] More preferably, the hyperbranched polyester is a mixture of HyPer C100 and HyPer C182 produced by Wuhan Hyperbranching, and the mass ratio of the two is (4:6) to (6:4).

[0029] HyPer C100 has an ideal anti-filler float-out effect, and can improve the fluidity and uniformity of the modified resin when compounded with a large proportion of recycled fillers. HyPer C182 has both internal and external lubrication functions, and can work with the former to achieve ideal high compatibility, making ultra-high molecular weight polyethylene highly compatible with recycled fillers and polyurethane. In addition, HyPer C182 also has a certain antioxidant effect, so the environmental stability of the product can be further improved after compounding.

[0030] More preferably, the preparation method of the filler particle powder is:

[0031] The components are mixed and placed in a twin-screw extruder for melt dispersion, followed by extrusion granulation, and crushed and dispersed to a particle size of ≤100 μm, to obtain the filler particle powder.

[0032] More preferably, the processing temperature range of the twin-screw extruder is 90-200° C., and the screw speed is 600-700 rpm.

[0033] Preferably, among the antioxidants, the mass ratio of the semi-hindered phenol antioxidant, the phosphite antioxidant and the sulfur antioxidant is 1:(0.7-0.8):(0.2-0.3).

[0034] Through the synergistic effect of three antioxidants with different antioxidant principles, the prepared polyurethane composite material can be guaranteed to have the expected environmental stability and avoid the accelerated degradation reaction of polyurethane caused by the recycled materials contained in the filler particle powder. If any one of them is missing or replaced, the performance of the product will be seriously weakened.

[0035] More preferably, the semi-hindered phenol antioxidant is antioxidant AO-80, the phosphite antioxidant is antioxidant 168, and the sulfur antioxidant is antioxidant 412S.

[0036] Preferably, the ultraviolet absorber is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0037] Although the presence of titanium dioxide in the recycled filler can inhibit the aging effect of ultraviolet rays to a certain extent, for the polyurethane matrix, it is still necessary to introduce a certain amount of ultraviolet absorber to achieve long-term light stability.

[0038] More preferably, the polyurethane composite material comprises the following components in parts by weight:

[0039] 80-90 parts of polyurethane, 10-20 parts of filler particle powder, 0.5-1 part of antioxidant, and 0.5-1 part of ultraviolet absorber.

[0040] Preferably, the polyurethane is a thermoplastic polyether polyurethane elastomer.

[0041] More preferably, the components of the polyurethane composite material further include but are not limited to at least one of an antistatic agent, a lubricant, a catalyst, a plasticizer, a flame retardant, a coupling agent, and a colorant, and the weight proportion of each component is 0.01 to 1 part.

[0042] It should be noted that, in addition to the above-mentioned key components, different processing aids may be introduced into the components of the polyurethane composite material of the present invention according to actual needs or production needs. For example, in order to improve the antistatic performance of the product, an antistatic agent such as carbon black with antistatic effect may be added to the product; in order to improve the flame retardancy of the product, a flame retardant such as organic aluminum with flame retardant effect may be added to the product; in order to give the product a different color, a colorant with coloring function such as azo red may be added to the product, etc. As long as it does not affect the efficacy of the key components of the present invention and the expected performance of the product, the type and amount of the added additives are not limited.

[0043] Another object of the present invention is to provide a method for preparing the polyurethane composite material, comprising the following steps:

[0044] The components are mixed and then placed in a twin-screw extruder for melt dispersion extrusion to obtain the polyurethane composite material.

[0045] Preferably, the processing temperature zone of the twin-screw extruder is 80-200° C., and the screw speed is 400-500 rpm.

[0046] During the preparation of the polyurethane composite material of the present invention, due to the differences in density, fluidity and compatibility between the TPU matrix and the ultra-high molecular weight polyethylene and the hyperbranched polyester, the modified resin coated on the surface of the filler particle powder will not be dispersed in large quantities in the polyurethane matrix during the processing process, and thus still maintains a state similar to that of the masterbatch filler, so that impurities in the recycled filler during the processing will not diffuse into the polyurethane matrix and cause thermal aging thereof.

[0047] Another object of the present invention is to provide application of the polyurethane composite material in the preparation of industrial pipelines.

[0048] Polyurethane (TPU) is a common material for preparing transmission pipelines. For example, water, oil and solid materials can be transported using TPU pipes. Polyurethane is also a common raw material for preparing power transmission pipelines. However, these pipes sometimes need to be exposed to light or high temperature, and even the transported materials themselves are at a relatively high temperature. Therefore, in addition to high initial mechanical strength, they are also required to have sufficient light resistance and moisture and heat resistance. On the other hand, TPU pipes are updated and iterated quickly, so to a certain extent, the production cost is relatively high. The polyurethane matrix used in existing TPU pipes is basically in a mature stage, and it is difficult to further reduce the cost. The polyurethane composite material of the present invention uses recycled fillers as components to prepare products, which can effectively reduce the production cost of the products. At the same time, based on a specific light-resistant and moisture-heat aging component system, the product has excellent environmental stability resistance, which fully reaches or even exceeds the performance level of polyurethane products prepared with traditional newly prepared fillers.

[0049] The beneficial effect of the present invention is that the present invention provides a polyurethane composite material containing recycled fillers, firstly the recycled fillers are inertly modified to prepare filler particle powder and introduced into a polyurethane matrix, and then a specific composite anti-aging agent is introduced into the polyurethane matrix, the obtained product not only has good light, humidity and heat aging resistance, but also has a higher degree of mechanical property improvement than the existing recycled polyurethane composite materials, and is equivalent to the newly prepared polyurethane composite products containing fillers. DETAILED DESCRIPTION

[0050] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.

[0051] Example 1

[0052] An embodiment of the polyurethane composite material containing recycled filler and a preparation method thereof according to the present invention comprises the following steps:

[0053] The components except the filler particle powder are mixed, and then placed into a twin-screw extruder from a main feed port for melting, and the filler particle powder is added to the auxiliary feed port for mixing and melt-dispersed extrusion to obtain the polyurethane composite material; the processing temperature section temperature of the twin-screw extruder is 80-200°C, and the screw speed is 480rpm.

[0054] The components of the polyurethane composite material are shown in Table 1.

[0055] Embodiments 2 to 9

[0056] An embodiment of the polyurethane composite material containing recycled filler and the preparation method thereof of the present invention is different from Embodiment 1 only in that the component composition of the polyurethane composite material is different, as shown in Table 1.

[0057] Comparative Examples 1 to 10

[0058] A polyurethane composite material and a preparation method thereof, which are different from Example 1 only in that the component composition of the polyurethane composite material is different, as shown in Table 2.

[0059] Among the components of the embodiments and comparative examples:

[0060] The polyurethane is a thermoplastic polyether polyurethane elastomer 9380A produced by Bayer, Germany;

[0061] Filler particle powder 1 is homemade, and the preparation method is as follows:

[0062] The recycled filler 1 and the modified resin are mixed in a ratio of 85:15 and placed in a twin-screw extruder for melt dispersion, followed by extrusion granulation, crushing and dispersion to a particle size of ≤100 μm, to obtain the filler particle powder 1, the average particle size of the filler particle powder 1 is 62 μm; the processing temperature range of the twin-screw extruder is 90-200° C., and the screw speed is 600 rpm;

[0063] The recycled filler 1 is a powder obtained by thermal separation, cleaning and grinding of a pipe containing high-melting-point glass fiber reinforced Polyplastics LAPEROSLCP T130 plastic provided by a pipe factory in Guangdong;

[0064] The modified resin is a mixture of ultra-high molecular weight polyethylene and hyperbranched polyester in a mass ratio of 6:4;

[0065] The ultra-high molecular weight polyethylene is ultra-high molecular weight polyethylene GUR 4056-3 produced by Celanese;

[0066] The hyperbranched polyester is a mixture of HyPer C100 and HyPer C182 produced by Wuhan Hyperbranching, and the mass ratio of the two is 5:5.

[0067] Filler particle powder 2 is homemade. The difference from filler particle powder 1 is that the preparation method is as follows:

[0068] The recycled filler 2 and the modified resin are mixed in a ratio of 85:15 and placed in a twin-screw extruder for melt dispersion, followed by extrusion granulation, crushing and dispersion to a particle size of ≤100 μm, to obtain the filler particle powder 1, the average particle size of the filler particle powder 1 is 65 μm; the processing temperature range of the twin-screw extruder is 90-200° C., and the screw speed is 600 rpm;

[0069] The recycled filler 2 is rutile titanium dioxide powder recycled by Dongguan Kunpeng Renewable Resources Recycling Co., Ltd., with an average particle size of 18 μm and a quantitative content of rutile titanium dioxide powder reaching 85 wt%.

[0070] Filler particle powder 3 is homemade. Different from filler particle powder 1, the preparation method is as follows:

[0071] The recycled filler 3 and the modified resin are mixed in a ratio of 85:15 and placed in a twin-screw extruder for melt dispersion, followed by extrusion granulation, crushing and dispersion to a particle size of ≤100 μm, to obtain the filler particle powder 1, the average particle size of the filler particle powder 1 is 63 μm; the processing temperature range of the twin-screw extruder is 90-200° C., and the screw speed is 600 rpm;

[0072] The recycled filler 3 is obtained by mixing the recycled filler 1 and the recycled filler 2 in a mass ratio of 5:5.

[0073] The filler particle powder 4 is homemade. Different from the filler particle powder 1, the modified resin is a mixture of ultra-high molecular weight polyethylene and hyperbranched polyester in a mass ratio of 9:1.

[0074] The filler particle powder 5 is homemade. Different from the filler particle powder 1, the modified resin is a mixture of ultra-high molecular weight polyethylene and hyperbranched polyester in a mass ratio of 3:7.

[0075] Filler particle powder 6 is homemade. Different from filler particle powder 1, the hyperbranched polyester is HyPer C100 produced by Wuhan Hyperbranching.

[0076] Filler particle powder 7 is homemade. Different from filler particle powder 1, the hyperbranched polyester is HyPer C182 produced by Wuhan Hyperbranching.

[0077] The filler particle powder 8 is homemade, and is different from the filler particle powder 1 in that the modified resin is ultra-high molecular weight polyethylene.

[0078] Filler particle powder 9 is homemade, and is different from filler particle powder 1 in that the modified resin is a hyperbranched polyester.

[0079] The filler particle powder 10 is homemade. The difference from the filler particle powder 1 is that the hyperbranched polyester is replaced by maleic anhydride grafted polyethylene wax 4351 produced by Clariant of equal mass.

[0080] The filler particle powder 11 is homemade, and is different from the filler particle powder 1 in that the ultra-high molecular weight polyethylene is replaced by an equal mass of thermoplastic polyether polyurethane elastomer.

[0081] The filler particle powder 12 is homemade. Different from the filler particle powder 1, the preparation method is as follows: the recycled filler 1 is crushed and dispersed to a particle size of ≤100 μm to obtain the filler particle powder 10.

[0082] The filler particle powder 13 is homemade. Different from the filler particle powder 1, the preparation method is as follows: the filler 2 is recycled, crushed and dispersed to obtain the filler particle powder 11.

[0083] The new filler is high melting point glass fiber reinforced Polyplastics LAPEROS LCP T130, which has an average particle size of 65μm after crushing.

[0084] Antioxidant 1 is a semi-hindered phenol antioxidant produced by Japan Aidi Co., Ltd., namely antioxidant AO-80.

[0085] Antioxidant 2 is phosphite antioxidant 168 produced by BASF.

[0086] Antioxidant 3 is sulfur antioxidant 412S produced by BASF.

[0087] Antioxidant 4 is hindered phenol antioxidant 1010 produced by BASF.

[0088] The ultraviolet absorber was bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate UV770.

[0089] Table 1

[0090]

[0091]

[0092] Table 2

[0093]

[0094]

[0095] Effect Example 1

[0096] In order to verify the use effect of the polyurethane composite material of the present invention, the products obtained in each embodiment and comparative example were injection molded into test blocks and the following tests were performed:

[0097] (1) Tensile strength: tested according to ISO 527-1-2012, with a test rate of 200 mm / min;

[0098] (2) Elongation at break: tested according to ISO 527-1-2012, with a test rate of 200 mm / min;

[0099] (3) Moisture and heat resistance: The product is aged for 200 h at a relative humidity of 70%, 120° C., and normal pressure. After aging, the tensile strength and elongation at break are tested again according to steps (1) and (2). The performance retention rate after aging is tested based on the test results before and after aging.

[0100] (4) Light aging test: The product is exposed to UVA-340 ultraviolet light for 360 hours at room temperature, pressure and humidity. After exposure, the tensile strength and elongation at break are tested according to steps (1) and (2). The performance retention rate after aging is tested based on the test results before and after aging.

[0101] (5) Appearance test: confirm whether cracks or powdering occurs on the sample surface after the treatment in the above steps (3) and / or (4).

[0102] The test results are shown in Table 3.

[0103] Table 3

[0104]

[0105]

[0106]

[0107]

[0108] It can be seen from the test results that the polyurethane composite material containing recycled fillers of the present invention is specially modified with recycled fillers and compounded with composite anti-aging agents, so that the prepared product not only has excellent basic mechanical properties, but also has a tensile strength of more than 42MPa and an elongation at break of more than 500%. In addition, in a wet heat aging test, after standing in a wet heat environment for 200 hours, the tensile strength retention rate of the product can reach more than 80%, and the elongation at break retention rate can reach more than 82%. In a light aging test, the retention rates of the tensile strength and elongation at break of the obtained product can reach more than 85%. The product has good environmental stability and no obvious appearance defects are found after the test. It can be seen from Examples 1, 4 and 5 that the modification method of the recycled filler in the product of the present invention is effective for both inorganic recycled fillers and organic composite recycled fillers, and based on the difference in the properties of the recycled fillers, the basic mechanical strength or environmental stability of the product is also different. Compared with the new plastic filler used in Comparative Example 10, the environmental stability of the recycled plastic filler in Example 1 after modification is basically the same as that of the product prepared from new materials, and based on the mechanical enhancement of the modified resin, the mechanical strength of the product is slightly higher than that of the product prepared from new materials, which fully demonstrates that the polyurethane composite material containing recycled fillers described in the present invention can completely replace the polyurethane composite material prepared from existing plastic fillers, and the production cost of the product will be significantly reduced.

[0109] In contrast, in the product of comparative example 1, no hyperbranched polyester is introduced when the recycled filler is modified, so that the compatibility of ultra-high molecular weight polyethylene with the recycled filler and the polyurethane matrix is ​​not ideal, and the anti-oxidation protection effect of the encapsulated resin on the product is also reduced, so the product is not only compared with the product of Example 1, but also the basic mechanical properties are reduced, and the moisture and heat resistance and light aging resistance are significantly reduced; the product of comparative example 2 is a hyperbranched polyester as an inclusion to encapsulate the recycled filler, but the density of this additive and the degree of improvement of the mechanical properties of the product are not as good as ultra-high molecular weight polyethylene, and it cannot be evenly wrapped on the surface of the recycled filler, and even when the filler particle powder is melt-mixed with the polyurethane, it quickly migrates to the polyurethane matrix, and the environmental resistance of the product is not ideal. In comparative example 3, the TPU lubricant / compatibilizer frequently used by technicians in this field is used instead of the hyperbranched polyester, and its environmental stability is improved to a certain extent compared with the product of comparative example 1, but the magnitude is not large, indicating that it is not suitable as a modified component of the recycled filler. In the product of Comparative Example 4, ultra-high molecular weight polyethylene is replaced with polyurethane elastomer. This approach not only reduces the basic mechanical strength of the product, but also can only slightly suppress the influence of impurities in the recycled filler on the polyurethane matrix during processing. Compared with Comparative Example 5 prepared directly using recycled organic composite fillers, the mechanical property retention rate of the product after wet heat and light aging treatment is not much different; Comparative Examples 5 and 6 prepare products with pure inorganic and organic composite fillers. It can be seen that the impurities in the filler have affected the performance of the product during processing, and due to the poor compatibility of the filler with the matrix resin, the product even has appearance problems after wet heat and light aging treatment and cannot be used directly. According to Example 1 and Comparative Examples 7 and 8, it can be seen that in addition to the modification of the recycled filler by the modified resin, the introduction of the composite anti-aging agent into the polyurethane composite material is also a key step for its environmental stability. The semi-hindered phenol + phosphite + sulfur antioxidant system is a necessary condition for the product to avoid the influence of impurities in the recycled filler to the greatest extent. If one of them is missing, or the typical antioxidant 1010 + antioxidant 168 system in the existing plastic system is used, the moisture and heat resistance of the product will be greatly reduced. In the product of Comparative Example 9, no ultraviolet absorber is introduced, and the performance retention rate of the product after light aging can only be maintained at about 70%, indicating that relying solely on the modified resin cannot inhibit the photodegradation catalysis of impurities in the recycled filler to the polyurethane matrix, and the use of ultraviolet absorbers is still a decisive factor for the photostability of the product.

[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A polyurethane composite material, characterized in that: The composition comprises the following components in parts by weight: 80-90 parts of polyurethane, 10-20 parts of filler particle powder, 1-2 parts of composite anti-aging agent; The filler particle powder is a recycled filler wrapped with modified resin; The modified resin includes ultra-high molecular weight polyethylene and hyperbranched polyester; The composite anti-aging agent includes an antioxidant and an ultraviolet absorber; The antioxidant is a compound of a semi-hindered phenol antioxidant, tris[2.4-di-tert-butylphenyl]phosphite and a sulfur antioxidant.

2. The polyurethane composite material according to claim 1, characterized in that: The recycled filler includes at least one of recycled inorganic filler and recycled organic composite filler.

3. The polyurethane composite material according to claim 2, characterized in that: The recycled inorganic filler is recycled titanium dioxide, and the average particle size of the recycled titanium dioxide is ≤20 μm; the recycled organic composite filler includes at least one of glass fiber reinforced polypropylene, glass fiber reinforced polyethylene, and glass fiber reinforced polyester.

4. The polyurethane composite material according to claim 1, characterized in that: The filler particle powder comprises the following components in parts by weight: 80-90 parts of recycled filler and 10-20 parts of modified resin; The modified resin is a composite of ultra-high molecular weight polyethylene and hyperbranched polyester, and the mass ratio of the two is (7:3) to (5:5).

5. The polyurethane composite material according to claim 4, characterized in that: The hyperbranched polyester is a mixture of HyPer C100 and HyPer C182 produced by Wuhan Hyperbranching, and the mass ratio of the two is (4:6) to (6:4).

6. The polyurethane composite material according to claim 1, characterized in that: In the antioxidant, the mass ratio of the semi-hindered phenol antioxidant, tris[2,4-di-tert-butylphenyl]phosphite and the sulfur antioxidant is 1:(0.7-0.8):(0.2-0.3).

7. The polyurethane composite material according to claim 6, characterized in that: The semi-hindered phenol antioxidant is antioxidant AO-80, and the sulfur antioxidant is antioxidant 412S.

8. The polyurethane composite material according to claim 1, characterized in that: The ultraviolet absorber is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

9. The method for preparing the polyurethane composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The components are mixed and then placed in a twin-screw extruder for melt dispersion extrusion to obtain the polyurethane composite material.

10. The method for preparing the polyurethane composite material according to claim 9, characterized in that: The processing temperature zone of the twin-screw extruder is 80-200° C., and the screw speed is 400-500 rpm.

11. Use of the polyurethane composite material according to any one of claims 1 to 8 in the preparation of industrial pipelines.

Citation Information

Patent Citations

  • Long glass fiber enhanced thermoplastic material and preparation method thereof

    CN108624032A

  • Thermooxidative aging resistant polypropylene functional master batch as well as preparation method and application thereof

    CN114940790A